2019
DOI: 10.15252/embj.2018101302
|View full text |Cite
|
Sign up to set email alerts
|

The tumor cell‐secreted matricellular protein WISP 1 drives pro‐metastatic collagen linearization

Abstract: Collagen linearization is a hallmark of aggressive tumors and a key pathogenic event that promotes cancer cell invasion and metastasis. Cell‐generated mechanical tension has been proposed to contribute to collagen linearization in tumors, but it is unknown whether other mechanisms play prominent roles in this process. Here, we show that the secretome of cancer cells is by itself able to induce collagen linearization independently of cell‐generated mechanical forces. Among the tumor cell‐secreted factors, we fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 62 publications
(158 reference statements)
1
42
0
Order By: Relevance
“…The force-mediated fibronectin assembly creates anisotropic fibre orientation and can open gaps in the matrix that allow cell migration 175 . Collagen linearization can also be mediated by tumour-secreted factors such as the WNT1 inducible signalling pathway gene (WISP1) 176 , which is triggered by TGF-β.…”
Section: Impact Of Tumourigenic Ecm Remodellingmentioning
confidence: 99%
“…The force-mediated fibronectin assembly creates anisotropic fibre orientation and can open gaps in the matrix that allow cell migration 175 . Collagen linearization can also be mediated by tumour-secreted factors such as the WNT1 inducible signalling pathway gene (WISP1) 176 , which is triggered by TGF-β.…”
Section: Impact Of Tumourigenic Ecm Remodellingmentioning
confidence: 99%
“…The aligned collagen fibers provide tracks not only for cancer cells but also for macrophages, thereby promoting their migration into the TME (124). Recently, WISP1, a matricellular protein secreted by cancer cells, was shown to induce collagen linearization by binding directly type I collagen, thereby promoting its linearization, independently of cell-derived mechanical tensions (125). Moreover, fibroblast activation protein (FAP), another important ECM-associated proteinase, promotes the formation in vitro of desmoplastic-like aligned matrices (126) and its overexpression has been associated with a poor patient outcome.…”
Section: Implications Of Fibrillar Collagens In Cancer Progressionmentioning
confidence: 99%
“…The POSTN family member MGP was recently shown to be incorporated into crosslinked multimers of fibronectin, which enhanced cancer cell attachment to fibronectin (23). As for the CCN family, recent studies have shown CCN1, CCN2 and CCN4 to promote alignment and stability of collagen fibers (13,157,176…”
Section: Mcp Biomechanical Effectsmentioning
confidence: 99%